Response of Chironomidae (Diptera) to DDT, Mercury, and Arsenic Legacy Pollution in Sediments of the Toce River (Northern Italy) - Laura Marziali; Niccolò Pirola; Alfredo Schiavon; Bruno Rossaro (Insects, 2024)
The Toce River (Northern Italy) is characterized by legacy contamination of dichloro-diphenyl-trichloroethane (DDT), mercury, and arsenic deriving from an industrial plant active between ca. 1915 and 1996. Chironomidae taxa assemblages and sediments were collected in 2014 and 2019 upstream and downstream of the industrial area to analyze species responses to toxic substances in a river stretch with relatively uniform natural (i.e., hydro-morphological) characteristics. A total of 32 chironomid taxa were identified. Sediment concentrations reached levels potentially toxic for benthic invertebrates: 15.7 µg kg−1 1% organic carbon for DDT, 197 µg kg−1 dry weight (d.w.) for Hg, and 55.7 mg kg−1 d.w. for As. Canonical Correspondence Analysis (CCA) revealed a predominant seasonal gradient, followed by an upstream-downstream gradient. Partial CCA indicated that 5.2% of the total variation was associated with sediment contamination. Self-Organizing Maps (SOMs) were used to represent species responses to toxicants. Most species appeared to be tolerant, e.g., Chironomus riparius, Micropsectra atrofasciata, Conchapelopia pallidula, and Polypedilum spp. Sensitivity to contaminants was observed in only a few species: Diamesa spp., Sympotthastia spinifera, and Prodiamesa olivacea to DDT; Potthastia longimanus to Hg; Odontomesa fulva and Microtendipes pedellus to As. The chironomid community was characterized in presence of contamination levels commonly observed in freshwater ecosystems.